A Bayesian Negative Binomial Hierarchical Model for Identifying Diet–Gut Microbiome Associations - Revers, Alma; Zhang, Xiang; Zwinderman, Aeilko H. (Frontiers in Microbiology, 2021)
The human gut microbiota composition plays an important role in human health. Long term diet intervention may shape human gut microbiome. Therefore, many studies focus on discovering links between long term diets and gut microbiota composition. This study aimed to incorporate the phylogenetic relationships between the OTUs into the diet-microbe association analysis, using a Bayesian hierarchical negative binomial (NB) model. We regularized the dispersion parameter of the negative binomial distribution by assuming a mean-dispersion association. A simulation study showed that, if over-dispersion is present in the microbiome data, our approach performed better in terms of MSE of the slope-estimates compared to the standard NB regression model or a Bayesian hierarchical NB model without including the phylogenetic relationships. Data of the Healthy Life in an Urban Setting (HELIUS) study showed that for some phylogenetic families the (posterior) variances of the slope-estimates was decreasing when including the phylogenetic relationships into the analyses. In contrast, when OTUs of the same family were not similarly affected by the food item, some bias was introduced, leading to larger (posterior) variances of the slope-estimates. Overall, the Bayesian hierarchical negative binomial model, with a dependency between the mean and dispersion parameters, proved to be a robust method for analyzing diet-microbe associations.